Prohibiting medically assisted procreation to gay couples is not illegitimate. (January 2020) - Cioffi, Andrea; Cioffi, Fernanda
Abstract: In Italy, the law n. 40 of 2004 ( Norms in matter of medically assisted procreation ), allows to access to the techniques of Medically assisted Procreation (MAP) exclusively to couples formed by two individuals of different sex. On the basis of this law, two couples of homosexual women were prohibited from using MAP techniques. For this reason, the couples have appealed to the competent courts that have raised doubts of constitutional legitimacy. In June 2019, the Italian Constitutional Court stated that it is not illegal to prohibit gay couples from accessing MAP techniques. In October 2019, the judgment No. 221, in which this decision is based, was published. Following the publication of the judgment, a bioethical-legal debate arose on this issue: is this a discrimination, or a simple limit based on medical-legal criteria? Highlights: Italian Constitutional Court confirmed the constitutionality of the prohibition of access to MAP techniques for gay couples The judges have asserted that the right to health does not mean to support every need of the individual or the couple A fundamental bioethical question re-emerges: is it the right of the unborn child to have two parents of the opposite sex?